2020
DOI: 10.47723/kcmj.v15i2.157
|View full text |Cite
|
Sign up to set email alerts
|

The Actual Practice of Breast Self-Examination among Sample of Iraqi Patients with Breast Cancer

Abstract: Background : To assess the actual practice of breast self-examination (BSE), as an early detection tool for breast cancer, among a sample of patients affected with breast cancer in Iraq.Methods: A random sample of 200 female patients with breast cancer was analyzed to evaluate the extent of their actual practice of breast self-examination before the diagnosis of the disease.  The examined variables included the age of the patients, marital status, education, occupation, smoking habit, family history of cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Understanding BSE procedures, recognizing signs of breast cancer, and fostering a proactive attitude towards self-examination can significantly impact early detection and encourage seeking medical advice promptly. In Iraq, studies have shown that while a high percentage of women diagnosed with breast cancer discover the disease themselves, it is often at advanced stages due to inadequate awareness and practice of BSE [11,12] . A study by the National Clinical Research Center (NCRC) found that half of the educated Iraqi women aware of BSE never practiced it, mainly due to unawareness of the correct techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding BSE procedures, recognizing signs of breast cancer, and fostering a proactive attitude towards self-examination can significantly impact early detection and encourage seeking medical advice promptly. In Iraq, studies have shown that while a high percentage of women diagnosed with breast cancer discover the disease themselves, it is often at advanced stages due to inadequate awareness and practice of BSE [11,12] . A study by the National Clinical Research Center (NCRC) found that half of the educated Iraqi women aware of BSE never practiced it, mainly due to unawareness of the correct techniques.…”
Section: Introductionmentioning
confidence: 99%